Analysis of the bmp Gene Family in Borrelia burgdorferi Sensu Lato - Gorbacheva, Victoria Y. (American Society for Microbiology, 2000)
BmpA, BmpB, BmpC, and BmpD are homologous Borrelia burgdorferi lipoproteins of unknown functions, encoded by the bmp genes of paralogous chromosomal gene family 36. At least some of the Bmp proteins are immunogens in infected vertebrate hosts. The genetic organization of the bmp region has been characterized for a variety of B. burgdorferi sensu lato strains by Southern hybridization, PCR amplification, and DNA sequencing. All four bmp genes were present in the same relative order in all B. burgdorferi sensu lato low- and high-passage-number isolates. While there were no differences in the relative orders of the bmp genes in these species, variations in DNA sequence in the bmpD-bmpC and bmpC-bmpA intergenic regions were significantly more common than in the corresponding 3′ bmpD and bmpC coding regions. The genetic structure of the chromosomal region containing the bmp genes thus appears to be well conserved across different species of B. burgdorferi, but variations in DNA fine structure that prevent PCR primer annealing may occur in this region and make Southern hybridization much more reliable than PCR for detection of the presence of these genes. Our results also suggest that bmp gene products may be used as reagents in the preparation of vaccines and diagnostic assays to protect against and diagnose Lyme disease produced by B. burgdorferi sensu lato.